LATIHAN OTOT DASAR PANGGUL DAN KOMUNIKASI SEKSUAL PADA IBU PASCASALIN - novita dewi pramanik (Jurnal Informasi Kesehatan Indonesia (JIKI), 2018)
Abstract This study aimed was to discover the effect of combination of Pelvic Floor Muscle Exercise (PFME) and sexual communication on improving postpartum sexual intercourse quality. Respondents was woman who’s in the range of 2-3 months postpartum. Research design uses concurrent embedded mixed methods. Quantitative phase using quasi-experimental pre-posttest control group design, while qualitative phase uses a phenomenological approach with in-depth interview techniques that seek information about the influence of PFME and sexual communication on postpartum sexual satisfaction. The Female Sexual Function Index (FSFI) questionnaire was used to measure 6 sexual dimensions that describe the quality of a sexual intercourse, that is sexual desire, sexual arousal, lubrication, orgasm, sexual satisfaction and pain during intercourse. Quantitative and qualitative analysis results showed improvement in sexual intercourse quality on both intervention and control groups (p <0.05). The results of in-depth interviews emphasize that psychological elements play an important role in improving the quality of postpartum maternal sexual intercourse, that facilitated through sexual communication interventions. Keywords: postpartum sexual intercourse, sexual communication, pelvic floor muscle exercise